Albumin Supplement Affects the Metabolism and Metabolism‐Related Drug–Drug Interaction of Fenoprofen Enantiomers. Issue 7 (3rd June 2015) - Wang, Nan; Wang, Feng; Meng, Yu; Yang, Guo‐Hui; Chen, Ju‐Wu; Wang, Jia‐Xiang
Abstract The influence of albumin towards the metabolism behavior of fenoprofen enantiomers and relevant drug–drug interaction was investigated in the present study. The metabolic behavior of fenoprofen enantiomers was compared in a phase II metabolic incubation system with and without bovine serum albumin (BSA). BSA supplement increased the binding affinity parameter (Km) of (R)‐fenoprofen towards human liver microsomes (HLMs) from 148.3 to 214.4 μM. In contrast, BSA supplement decreased the Km of (S)‐fenoprofen towards HLMs from 218.2 to 123.5 μM. For maximum reaction velocity (Vmax), the addition of BSA increased the Vmax of (R)‐fenoprofen from 1.3 to 1.6 nmol/min/mg protein. In the contrast, BSA supplement decreased the Vmax value from 3.3 to 1.5 nmol/min/mg protein. Andrographolide–fenoprofen interaction was used as an example to investigate the influence of BSA supplement towards fenoprofen‐relevant drug–drug interaction. The addition of 0.2% BSA in the incubation system significantly decreased the inhibition potential of andrographolide towards (R)‐fenoprofen metabolism (P < 0.001). Different from (R)‐fenoprofen, the addition of BSA significantly increased the inhibition potential of andrographolide towards the metabolism of (S)‐fenoprofen. BSA supplement also changed the inhibition kinetic type and parameter of andrographolide towards the metabolism of (S)‐fenoprofen. In conclusion, albumin supplement changes the metabolic behavior of fenoprofen enantiomers and the fenoprofen–andrographolide interaction. Chirality 27:436–440, 2015. © 2015 Wiley Periodicals, Inc.